Estudo da contratilidade de segmentos isolados de esôfago e estômago de fetos de ratas sujeitos a modelo experimental de atresia de esôfago induzida por doxorrubicina - Capeto, Fabíola Araújo (2014)
Esophageal atresia (EA) is a structural anomaly that results from an incomplete esophago-traqueal septation in the fetus during intrauterine development. The in vitro contractility of the distal esophagus and gastric fundus of fetuses with esophageal atresia induced by Doxorubicin (Doxo) was studied. 26 Female Wistar rats (267 g), were subjected to date-controlled mating, subsequently receiving 2.2 mg/kg Doxo intraperitoneally on days 8 and 9 of pregnancy, while a controlled group of 13 rats received the same volume of 0.9% NaCl. On day 21.5 the pregnant rats were submitted to a cesarean surgery, with the fetuses analysed to confirm EA and thereafter divided into 3 groups: control, whose mothers received only 0.9% NaCl; Doxo without EA, whose mothers received Doxo but not developed EA; Doxo with EA, who developed EA. After being sacrificed, ring-strips of the gastric fundus were obtained from the fetuses and mounted in isolated organ bath, while the distal esophageal strips were mounted in wire myograph system; both strips contained a standard Tyrode solution maintained at 37 °C, pH 7.4, in addition to constant oxygenation and a basal tension of 1 g for the fundic strips and 8 mN for the esophagus. For each set up, we carried out a cholinergic-agonist concentration- effect curve with Carbachol (CCh) (0.01 – 300 μM) in both tissue in the three groups. The participation of voltage-operated channels (VOCs) was studied; a KCl- concentration-effect curve (10 – 100 mM) was conducted on isolated esophageal strips. Collected data was subjected to two-way analysis of variance (ANOVA) and the significance was tested using Student-Newman-Keuls test. There was not significant statistical difference in fundic strips’ contractility in response to CCh (p>0.05, ANOVA), the EC50 values of the control animals were 2.17 [1.03 – 4.58] μM and Emax 0.084 ± 0.016 g/mg tissue (n=7); Doxo without EA 1.47 [0.83 – 2.61] μM and 0.068 ± 0.006 g/mg tissue (n=12); Doxo with EA 3.26 [1.90 – 5.60] μM and 0.070 ± 0.022 g/mg tissue (n=6). However, significant statistical difference was noted (p<0.05, ANOVA), in esophageal strips’ contractility in response to CCh in the Emax value of control 5.97 ± 0.58 mN (n=11), vs Doxo without EA 4.48 ± 0.34 mN (n=11) and Doxo with EA 4.42 ± 0.68 mN (n=8), while there was not significant statistical difference (p>0.05, ANOVA) in the EC50 value of control 190 [96 – 379] nM, Doxo without EA 228 [125 – 418] nM and Doxo with EA 439 [206 – 936] nM. Tensional response to KCl were present in all groups, though lower than that seen in response ￼to CCh, however not statistically different when comparing all the three groups (p>0.05, ANOVA), Emax of control was 1.31 ± 0.14 mN (n=5), Doxo without EA 1.27 ± 0.42 mN (n=7) and Doxo with EA 1.21 ± 0.20 mN (n=7). It is possible to conclude that the treatment of rats with Doxo during pregnancy leads to decrease contractility of isolated esophagus of their fetuses, independent of the development of EA. Apparently, such a decrease is not due to a lower functionality of VOC channels. The isolated gastric fundus strips showed no change in contractile response.